Financial Reporting Quality on Indonesia Islamic Banks: An Internal Stakeholders Perception - R. Rini (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2014)
This study describes financial reporting quality of 33 Islamic Banks in Indonesia. The data was taken by questionnaires from 173 respondents, consist of employees (head of group, head of division, and internal auditor), audit committee members, and sharia supervisory board members. The questionnaires consist of 24 questions with eight dimensions of research instruments, they are financial reporting quality (ie. timeliness, verifiability, completeness, representation faithfulness, neutrality, comparability, consistency and clarity). This research is qualitative, therefore using interpretive analysis as data analysis. The result shows that representative faithfulness is considered as the most important component by internal party of Islamic banks.